2015
DOI: 10.1080/07391102.2015.1071280
|View full text |Cite
|
Sign up to set email alerts
|

Probing the biological evaluations of a new designed Pt(II) complex using spectroscopic and theoretical approaches: human hemoglobin as a target

Abstract: In recent years, using heavy metal compounds such as platinum as anticancer agent is one of the common ways in chemical therapy. In this study, a new anticancer compound of glycine derivatives of Pt(II) complex (amyl-glycine1, 10-phenanthroline Platinum nitrate) was designed, and the biological effects of this novel compound on the alterations in the function and structure of human hemoglobin (Hb) at different temperatures of 25 and 37°C were assessed by applying various spectroscopic (fluorescence and circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Recently, piperine’s potential cytotoxic and anti-tumorigenic properties in against several types of cancer cells have been reported ( 15 ). In recent years, numerous experiments in vitro and vivo have reported that the anti-tumor activity of piperine may partly be due to its effects on signaling pathways involved in apoptosis of cancer cells ( 15 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, piperine’s potential cytotoxic and anti-tumorigenic properties in against several types of cancer cells have been reported ( 15 ). In recent years, numerous experiments in vitro and vivo have reported that the anti-tumor activity of piperine may partly be due to its effects on signaling pathways involved in apoptosis of cancer cells ( 15 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the effect of silibinin was examined on the serum indicators of liver tissue injury, as well as Cx43, Cx32, and Cx26 gene expression during warm hepatic IR. The IRI frequently occurs during transplantation and hepatic surgery; moreover, it promotes molecular reactions that enhance damage in the liver parenchyma (22)(23)(24). Several studies reported that GJ proteins are involved in liver IRI (7,25).…”
Section: Discussionmentioning
confidence: 99%
“…Several reported works explain the interaction of the various compounds with Hb. Such as oxali‐palladium, [13] Pt(II) complex, [14] etc., anion exchange inhibitor, e. g., DIDS & antiseptic drug, e. g., DNP [5a] . Nevertheless, there are few reports which study the interaction between Hb and anticancer drug directly [7c,d] …”
Section: Introductionmentioning
confidence: 99%